STANDARDIZATION OF ZEOLITE MINERAL FOR QUALITY CONTROL - Astiana Sastiono (Jurnal Zeolit Indonesia, 2002)
Zeolite minerals in the past 20 years have been used n many aspect of agriculture, industry and environmental protection. Application of zeolites commercially depends on one or more of their physical and chemical characteristics. Natural zeolites are obtained as tuff rocks together with other minerals with the variation in their composition. Separation of the mineral is very difficult with any chemical process. In order to guarantee the quality of natural zeolites as a commercial product, we need to establish national standard of zeolites. Properties of zeolite such as particle size, mineral compositions, chemical properties and other properties need to be standardized.